Dampak Penggunaan Media Sosial terhadap Perilaku Sosial dalam Literasi Digital Generasi Z - Dewi Affyati; Siti Wardatunnisa; Himayatu Zakiyah; Teresa Stefny Valentine; Yunita Rahmadhani; Alfi Nursyifa (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
The rise of social media has introduced notable transformations in the ways Generation Z communicates and behaves socially. This cohort has been raised within a digital landscape, which has turned social media into a platform for not just entertainment, but also for interaction, searching for information, education, expressing oneself, and forming social identities. This research seeks to explore how social media usage influences the social conduct of Generation Z through the lens of digital literacy. The approach taken is a literature review utilizing a qualitative method, involving the gathering and examination of pertinent materials, including academic journals, articles, and earlier research results. The findings reveal that social media has beneficial effects, such as facilitating communication, expanding social networks, enhancing creativity, and promoting involvement in online environments. On the flip side, overusing social media can result in adverse effects such as diminished in-person communication, reliance on digital platforms, a desire for social approval, and susceptibility to false information and scams. Consequently, fostering digital literacy is crucial for empowering Generation Z to engage with social media in a critical, thoughtful, safe, and responsible manner.